Kinetic Degradation of Myristicin, Elemicin, and Safrole in Encapsulated Banda Nutmeg (Myristica fragrans Houtt) Oleoresin - Dewi Amrih; Chusnul Hidayat; Pudji Hastuti (Indonesian Food and Nutrition Progress, 2017)
Spices, in the form of oleoresin, have advantages as a flavoring agent. Nutmeg oleoresin compounds that play an important role in the formation of nutmeg flavor are myristicin, elemicin, and safrole. These compounds are not stable, so that the quality of oleoresin decreased easily. An alternative to overcome this problem is the encapsulation of oleoresin using spray drying techniques. The objective of this research was to evaluate the physicochemical properties of oleoresin with respect to the degradation of myristicin, elemicin, and safrole of nutmeg oleoresin. Microencapsulated nutmeg oleoresin was prepared using 12% WPC and 88% maltodextrin as encapsulate materials. It was stored in dark glass bottles at a various temperature, namely 30°C, 40°C, 50°C, 60°C, and 70°C, for 0, 4, 7, 10, 14, 21, 28, 35, 42, 49, 56 and 63 days. The content of myristicin, elemicin, and safrole were analysed. The results showed that myristicin, elemicin, and safrole in the encapsulated nutmeg oleoresin decreased during the storage until 28 days of storage and then they were relatively stable until 63 days. The activation energy of myristicin, elemicin, and safrole were 2.21 kJ/mol.K, 2.71 kJ/mol.K and 3.22 kJ/mol.K, respectively.